2003
DOI: 10.1021/ma021509c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Exfoliation of Nanoclay Particles in Epoxy−Clay Nanocomposites

Abstract: The mechanism of nanoclay exfoliation was investigated in epoxy-clay nanocomposites system. The elastic force exerted by cross-linked epoxy molecules inside the clay galleries was found responsible for exfoliation of clay layers from the intercalated tactoids. Complete exfoliation of clay galleries was observed under the conditions of slow increase of complex viscosity and fast rise of storage modulus. It was observed that faster intragallery polymerization, though expedited the exfoliation process, was not ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
202
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(211 citation statements)
references
References 46 publications
5
202
0
4
Order By: Relevance
“…In recent years numerous research activities on polymer-clay nano-composites have been performed. However, the matrices of polymer-clay nanocomposites are mainly synthetic thermosetting [177][178][179] as well as thermoplastics polymers [180][181][182][183][184][185] but of late biodegradable plastics have found place even though limited, for example, PlA 186 and PCl 187 have also been used for the processing of nanocomposites with a layered silicate. However, the materials prepared from natural polymers have poor performance compared with those prepared from synthetic polymers.…”
Section: Bio Nano-compositesmentioning
confidence: 99%
“…In recent years numerous research activities on polymer-clay nano-composites have been performed. However, the matrices of polymer-clay nanocomposites are mainly synthetic thermosetting [177][178][179] as well as thermoplastics polymers [180][181][182][183][184][185] but of late biodegradable plastics have found place even though limited, for example, PlA 186 and PCl 187 have also been used for the processing of nanocomposites with a layered silicate. However, the materials prepared from natural polymers have poor performance compared with those prepared from synthetic polymers.…”
Section: Bio Nano-compositesmentioning
confidence: 99%
“…[31][32][33] Acetone, which was used as a dispersing agent for nanoclay, can easily penetrate clay galleries and enable epoxy resin to be placed between clay layers before the curing process.…”
Section: Structure Characterizationmentioning
confidence: 99%
“…Park and Jana [29] investigated the mechanism of exfoliation of nanoclay particles in epoxy-clay nanocomposites. They suggested that the elastic force exerted by crosslinked epoxy molecules in the clay galleries were responsible for exfoliation of clay layers from the intercalated tactoids.…”
Section: The Role Of Intercalation and Diffusionmentioning
confidence: 99%